Controllable preparation method of molecular welding zeolite coating with high adsorption capacity in extreme environment

Through molecular welding strategies, the zeolite molecular sieve is modified to generate active groups and coordinately match the pore structure, which solves the problem of low adsorption capacity of the zeolite adsorption coating with poor binding force and substrate in extreme environments, and achieves high adsorption capacity and strong binding force.

CN119592111APending Publication Date: 2025-03-11HARBIN INST OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411757382.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The problem of low adsorption capacity of zeolite adsorption coating in extreme environments and poor binding force with the substrate.

Method used

Using molecular welding strategy, zeolite molecular sieve is modified by gallic acid to generate hollow structures and generate active groups on the surface, enhance interface binding force, and reduce mass transfer resistance through synergistically matched pore structures to promote the adsorption and diffusion of molecular pollutants.

Benefits of technology

It significantly improves the adsorption capacity and interface binding capacity of the coating in extreme environments, enhances the adsorption capacity to molecular pollutants, and improves the overall binding and adhesion of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592111A_ABST
    Figure CN119592111A_ABST
Patent Text Reader

Abstract

The invention discloses a controllable preparation method of a molecular welding zeolite coating with high adsorption capacity in an extreme environment, and belongs to the field of special functional coatings. The invention aims to solve the problems of low adsorption capacity and poor binding force with a substrate of a zeolite adsorption coating in an extreme environment. The method comprises the following steps: 1, adding zeolite into a gallic acid solution, heating and stirring for reaction, washing, and filtering to obtain modified zeolite molecular sieve powder; 2, mixing the modified zeolite molecular sieve powder and silica sol to form spraying slurry; and 3, coating the surface of a substrate with the slurry obtained in the step 2, and curing to obtain the coating on the surface of the substrate. According to the method, a molecular welding strategy is adopted, precise regulation and control of a zeolite pore channel structure and a two-phase interface are achieved, and the limitation that adsorption performance and binding force in a molecular adsorption thermal control coating alternately change is broken through. The method can be widely applied to the fields of air purification, sewage treatment, aerospace, pollution protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of special functional coatings, and specifically relates to a controllable preparation method of a molecularly welded zeolite coating with high adsorption capacity under extreme environments. The coating prepared by the method of the present invention is a hierarchical porous adsorption coating, which has very broad application prospects in the fields of air purification, sewage treatment, aerospace, pollution protection, etc. Background Art

[0002] Once in orbit, spacecraft are in an extreme environment of high vacuum. Volatile organic gas molecules in their materials will be continuously released, causing serious contamination to sensitive surfaces of precision payloads such as optical imagers and lasers. On-orbit molecular contamination seriously reduces the performance of spacecraft hardware and shortens the service life of spacecraft. With increasingly stringent requirements for spacecraft quality and reliability, contamination control has gradually become one of the key factors for the success of most space missions. At present, the effective solution for contamination control is the adsorption method, which has the advantages of low cost and no power consumption. As an emerging sprayable coating, molecular adsorption coating can be directly sprayed onto the internal surface of the spacecraft, with the advantages of easy implementation, light weight and low cost.

[0003] Although molecular adsorption coatings have incomparable advantages, in practical applications, they still require clever structural design to solve the problems of low adsorption capacity and poor binding force with the substrate in extreme environments. The narrow microporous structure of zeolite limits the diffusion process of pollutants, and it is necessary to perform certain structural regulation to improve the adsorption capacity in extreme environments. At the same time, the binding force between zeolite and silica sol needs to be further improved to meet the practical application needs in extreme environments. Summary of the invention

[0004] The present invention aims to solve the problem of low adsorption capacity and poor binding force with substrate of zeolite adsorption coating under extreme environment, and provides a controllable preparation method of molecular welding zeolite coating with high adsorption capacity under extreme environment. The molecular welding strategy is used to achieve the coordinated matching combination of pore structure and the enhancement of group effect, and at the same time improve the adsorption capacity of the coating and the bonding ability between interfaces.

[0005] The coating described in the present invention is a graded porous adsorption coating and has very broad application prospects in the fields of air purification, sewage treatment, aerospace, pollution protection, etc.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The present invention adopts a molecular welding strategy to achieve precise control of the zeolite pore structure and the two-phase interface. The hydroxyl and other active groups generated on the surface of the modified zeolite are combined with the surface of the silica sol binder through hydrogen bonds to enhance the binding force; the synergistically matched pore structure reduces mass transfer resistance and promotes the adsorption and diffusion of molecular pollutants. The present invention breaks through the problem of zeolite micropores restricting diffusion by synergistically modifying pore bonding and surface chemical activity, breaking the limitation of the trade-off between adsorption performance and binding force in molecular adsorption thermal control coatings.

[0008] The object of the present invention is to provide a controllable preparation method of a molecularly welded zeolite coating having a high adsorption capacity under extreme environments, comprising the following steps:

[0009] Step 1: adding zeolite to gallic acid solution, heating and stirring to react, washing and filtering to obtain modified zeolite molecular sieve powder;

[0010] Step 2: Mixing the modified zeolite molecular sieve powder and silica sol to form a spray slurry;

[0011] Step three: apply the slurry obtained in step two on the surface of the substrate and solidify it to obtain the coating on the surface of the substrate.

[0012] It is further defined that in step 1, the gallic acid solution is prepared according to the following operation: a certain amount of gallic acid is added to a certain amount of deionized water, and stirred at 70° C. to 90° C. for 5 min to 30 min to obtain the gallic acid solution.

[0013] In a further embodiment, magnetic stirring is used during the preparation of the gallic acid solution.

[0014] It is further defined that in step 1, the mass fraction of the gallic acid solution is 1%-5%.

[0015] It is further defined that in step one, the zeolite is a low silicon-aluminum ratio zeolite, including but not limited to 13X zeolite and 5A zeolite.

[0016] It is further defined that in step 1, zeolite is added to the gallic acid solution at a mass concentration of zeolite of 5% to 20%.

[0017] It is further defined that in step 1, the reaction is heated and stirred at 80°C-90°C and a stirring rate of ≥400r / min for 0.5h-5h.

[0018] It is further defined that in step 2, the mass ratio of the modified zeolite to the silica sol is 0.3:1 to 3:1.

[0019] It is further defined that in step 2, the silica sol is acidic silica sol.

[0020] It is further defined that in step 2, spraying is performed after mixing and stirring for 3h-8h.

[0021] It is further defined that in step three, the coating substrate used can be a metal substrate such as aluminum alloy; it can also be a resin substrate or an organic-inorganic composite material substrate.

[0022] It is further defined that the coating preparation process used in step three has a spraying pressure of 0.6Mpa-1.5Mpa, a moving speed of the spray gun of 30cm / s-150cm / s, and a spray distance of 5cm-30cm; the composite coating is formed by multiple sprayings, and the thickness can be adjusted within 500 microns.

[0023] It is further defined that curing is to place the product in a fume hood at room temperature and air dry it for 8 to 16 hours, then heat it to 120° C. and cure it for 6 to 12 hours.

[0024] A molecularly welded zeolite coating having high adsorption capacity under extreme environments prepared by any of the above methods.

[0025] The purpose of the present invention is to prepare a molecular welding zeolite coating with high adsorption capacity under extreme environments. Through an ingenious molecular welding strategy, the zeolite molecular sieve is modified by gallic acid to generate a hollow structure and generate more active groups such as hydroxyl groups on the surface. The active groups realize the interface enhanced bonding coupling effect, which can realize the directional arrangement of the pore structure and promote the bonding between zeolite and silica sol, and finally improve the adsorption amount and bonding force of the coating under extreme environments. The coating can be directly applied to the inner surface of various precision equipment such as spacecraft by spraying.

[0026] Compared with existing adsorption materials, the present invention has higher adsorption capacity and stronger binding ability with the substrate under extreme environment. The present invention has the following beneficial effects:

[0027] The present invention uses gallic acid as a bridge molecule, which generates polar groups such as hydroxyl groups on the surface of zeolite after combining with the zeolite, and couples with the silica sol binder through the interaction between the groups to achieve enhanced interface bonding and enhance the overall bonding strength of the coating.

[0028] The present invention forms a three-dimensional graded trap pore structure by combining gallic acid and silica sol through the combination of pore structures of different sizes, thereby promoting the diffusion and adsorption of molecular pollutants in zeolite, so that the coating has a higher adsorption capacity for molecular pollutants under extreme environments.

[0029] The method of the invention is simple to operate and easy to implement, can be prepared on a large scale, and is conducive to practical engineering applications.

[0030] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a SEM image of the modified FAU zeolite prepared by the method of Example 1;

[0032] Figure 2 is a physical picture of the coating prepared by the method of Example 1;

[0033] Figure 3 is a SEM image of the coating prepared by the method of Example 1;

[0034] Figure 4 1 is the XRD pattern of the coating with different pigment-to-base ratios prepared by the method of Example 1;

[0035] Figure 5 is the nitrogen isotherm adsorption-desorption curve of the coating prepared by the method of Example 1;

[0036] Figure 6 is a NLDFT method differential integral logarithmic pore volume pore size distribution diagram of the coating prepared by the method of Example 1;

[0037] Figure 7 This is a graph of the adsorption amount of the coating prepared by the method of Example 1. DETAILED DESCRIPTION

[0038] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0039] Example 1: In this example, the controllable preparation method of the molecularly welded zeolite coating with high adsorption capacity under extreme environment is achieved by the following steps:

[0040] (1) Preparation of gallic acid solution:

[0041] 4 g of gallic acid was added to 100 g of deionized water, placed in a magnetically stirred reactor, and stirred for 15 min at 80° C. and a stirring speed of 500 r / min to obtain a gallic acid solution.

[0042] (2) Preparation of modified zeolite:

[0043] 5 g of zeolite was added to the gallic acid solution obtained in step (1), and the mixture was stirred at 80° C. and a stirring speed of 500 r / min for 30 min. The mixture was washed with deionized water and filtered to obtain a modified zeolite.

[0044] (3) Slurry preparation:

[0045] Under the condition of stirring speed of 500r / min, 10g of modified zeolite was slowly and evenly introduced into 50g of silica sol, and mechanical stirring was continued for 5h after the addition was completed.

[0046] (4) Slurry spraying:

[0047] In this embodiment, an aluminum alloy sheet is used as the substrate, and its surface is roughened by sandblasting, and then ultrasonically cleaned with anhydrous ethanol for 10 minutes. After cleaning, a dust-free cloth is dipped in anhydrous ethanol to wipe the surface clean. The slurry used for spraying is added to the liquid storage tank of the ultrasonic-assisted thermal spraying device, and the cavitation effect of the ultrasonic wave is used to promote further uniform mixing of the slurry, and the coating is sprayed on the surface of the aluminum alloy substrate. The spraying conditions are: the nozzle diameter is 2.5mm, the liquid delivery pressure is 0.7Mpa, the moving speed of the spray gun is 80cm / s, and the spray distance is 5cm.

[0048] (5) Curing and molding:

[0049] The obtained coating was placed in a fume hood at room temperature to dry naturally for 12 hours, and then placed in a vacuum oven for programmed heating to 100°C and then heated for curing for 10 hours to obtain a molecularly welded zeolite coating with high adsorption capacity in extreme environments.

[0050] The test results of the scanning electron microscope of the modified 13X zeolite obtained in this example are as follows: Figure 1 As shown, before modification, it is a smooth regular octahedron, and after modification, it is a hollow structure, which is conducive to the adsorption of spatial molecular pollutants.

[0051] The actual picture of the modified 13X zeolite obtained in this example is as follows Figure 2 As shown, the coating surface has a rough structure, which is relatively uniform and flat as a whole, without any peeling or flaking.

[0052] The test results of the coating scanning electron microscope obtained in this embodiment are as follows: Figure 3 As shown, the coating has a hierarchical porous surface structure, which is beneficial to the transmission, diffusion and adsorption of spatial molecular pollutants.

[0053] The XRD test results of the coatings with different pigment-to-base ratios obtained in this embodiment are as follows: Figure 4 As shown, obvious 13X zeolite crystal characteristic diffraction peaks can be observed, proving that the zeolite in the material has a high degree of crystallinity.

[0054] The nitrogen isothermal adsorption-desorption curve test results of the coatings with different pigment-to-base ratios obtained in this embodiment are shown in the figure below. Figure 5 As shown in Figure 2, according to the BET method, the specific surface area is 437.6 m 2 / g, the large specific surface area is conducive to the adsorption of space pollutant molecules.

[0055] The pore size distribution diagram of the coating obtained in this embodiment is as follows: Figure 6 As shown, it has both micropores of 0.7 nm and mesopores of about 4 nm. The graded trap-domain pore structure is conducive to the adsorption of spatial pollutant molecules.

[0056] The molecular adsorption coating material obtained in Example 1 before and after modification and the typical molecular pollutant dioctyl phthalate were placed in a space molecular pollution vacuum test system, and the temperature of the heating table was set to 60°C. The adsorption experiment was carried out on the heating table, and after 88 hours, the precision balance in the glove box was placed for weighing, and the adsorption amount was obtained by calculating the difference before and after weighing. The results are shown in Figure 7 As shown, the adsorption amount is from 3.0123 mg / cm 2 Increased to 5.1234mg / cm 2 , proving that the adsorption coating prepared by this method has a significant improvement in adsorption capacity. The modified coating showed significant enhancement in both hardness and elastic modulus, with the hardness increasing from 0.32 to 0.44 and the elastic modulus increasing from 5.4 to 9.4. After 50 tape stripping cycles, the coating surface remained intact, demonstrating its strong adhesion.

[0057] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.

Claims

1. A controllable preparation method of a molecularly welded zeolite coating with high adsorption capacity under extreme environments, characterized in that: The following steps are involved: Step 1, adding zeolite to gallic acid solution, heating and stirring to react, washing and filtering to obtain modified zeolite; Step 2: preparing a slurry of the modified zeolite and the silica sol; Step three: apply the slurry obtained in step two on the surface of the substrate and solidify it to obtain the coating on the surface of the substrate.

2. The method according to claim 1, characterized in that: The gallic acid solution is prepared according to the following operation: gallic acid is added into deionized water, and stirred at 70° C. to 90° C. for 5 min to 30 min to obtain the gallic acid solution.

3. The method according to claim 1, characterized in that: The mass fraction of the gallic acid solution is 1%-5%.

4. The method according to claim 1, characterized in that: The zeolite is a low silicon to aluminum ratio zeolite.

5. The method according to claim 1, characterized in that: In step 1, the mass concentration of zeolite is 5%-20%.

6. The method according to claim 1, characterized in that: In step 1, the reaction is heated and stirred at 80° C.-90° C. and a stirring rate of ≥400 r / min for 0.5 h-5 h.

7. The method according to claim 1, characterized in that: In step 2, the mass ratio of modified zeolite to silica sol is 0.3:1 to 3:

1.

8. The method according to claim 1, characterized in that: The silica sol is acidic silica sol.

9. The method according to claim 1, characterized in that: The curing is carried out by naturally air-drying at room temperature for 8 to 16 hours, and then heating to 120°C and curing for 6 to 12 hours.

10. A molecularly welded zeolite coating having high adsorption capacity under extreme environments prepared by the method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Molecular adsorption-thermal control bifunctional coating and preparation method thereof

    CN110499047A

  • Preparation method of polyphenol compound for removing heavy metal ions in water body

    CN117582949A

  • Polyphenol modified iron metal wire light zeolite, preparation method and application thereof, modified carbon felt, and preparation method and application thereof

    CN119016030A